Comparative evaluation on calcium silicate and rice husk ash amendment for silicon-based fertilization of Malaysian rice (Oryza sativa L.) varieties - Mahmad-Toher, Ainu-Shahirah; Govender, Nisha; Dorairaj, Deivaseeno; Mui, Yun Wong (Taylor and Francis, 2021)
Rice (Oryza sativa L.) is the most important staple food in the South-east Asian region as a dominant portion of global rice supply is produced and consumed here. Rice plant is a high silicon (Si) accumulator. Constitutive deposition of Si in the form of “phytoliths” offers the plant resistance against various pests, pathogens and stresses, and enhances growth and development. In this study, two sources of Si namely calcium silicate (CaSiO3) and rice husk ash (RHA) were comparatively evaluated for their bio-fertilizing efficiencies on rice plants cultivated under a glasshouse condition. In addition, we added manganese (Mn), as a form of supplemental nutrient and tested it in combination with the two Si sources. A two-factorial pot experiment with Malaysian rice varieties (MR219 and MR253) and Si-based treatment combinations [NPK only (control), NPK + RHA, NPK + CaSiO3, NPK + RHA + manganese (Mn) and NPK + CaSiO3+Mn] indicated that soil amendment using both, a renewable and nonrenewable Si compound (with and without Mn) significantly improved the rice yield-related components and yield as compared to the control (Si-free treatment) at P < 0.05. At 100 day after planting (harvest stage), the grain yield per experimental pot (MR219 and MR253 rice varieties) treated with RHA (with and without Mn) showed no significant difference to the plants treated with CaSiO3 (with and without Mn). Our findings suggest that RHA, an excellent renewable source fetched from rice production system offers an environmentally sound solution for effective Si-based fertilization of rice plants (Malaysian varieties).